PENGARUH HARGA REFERENSI, FREE GIFT, KEMASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN KUALITAS PRODUK SEBAGAI VARIABEL INTERVENING - Apriyani Simarmata, Lenny; Nanda Lestari, Rizky; Sarwoto, Sarwoto; Cai Cen, Cia (Berajah Journal, 2024)
This research aims to analyze the influence of reference prices, free gifts, product packaging on purchasing decisions and their implications for product quality. The method used is a quantitative method with Smart PLS 4.0 software. The sampling technique used was non-probability sampling with accidental sampling technique. Data were collected using a questionnaire and literature study for 83 respondents who had purchased and used Baba Parfum at the LAS Baba Parfum Shop. The data analysis method in this research uses multiple linear regression analysis and determinant coefficients with the research results namely that price influences purchasing decisions. The free gift has no influence on purchasing decision. Product packaging has no influence on purchasing decisions. Product quality influences purchasing decisions. Reference prices affect the quality products. The free gift has no effect on the quality of the LAS Baba Parfum shop products. Product packaging has no influence on purchasing decisions at the LAS Baba Parfum shop. Reference prices have no effect on purchasing decisions with product quality as an intervening variable. Free gifts have no effect on purchasing decisions with product quality as an intervening variable. Product packaging has no effect on purchasing decisions with product quality as an intervening variable.